A two-infection stage model with SIS and SIR dynamics - Sangotola*, A.O.; Sangoyinka†, L.J. (International Journal of Mathematical Analysis and Modelling, 2023)
A two-infection stage model is presented in this research work. The dynamics of the model is such that it behaves like a SIS or SIR model depending on the stage treatment is applied. The disease-free equilibrium point and the basic reproduction number are determined. The conditions for the disease-free equilibrium and endemic equilibrium to be globally asymptotically stable are determined. Sensitivity analysis is used to determine the impact of the model parameter on the basic reproduction number. Numerical simulation with suitable approximated parameters using MATLAB is also carried out to give possible dynamics of the model.